2022
DOI: 10.2217/fca-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Rate Versus Rhythm Control for Atrial Fibrillation: From Affirm to EAST-AFNET 4 – a Paradigm Shift

Abstract: The clinical choice between rate or rhythm control therapies has been debated over the years. In 2002, the AFFIRM trial demonstrated that the rhythm-control strategy had no survival advantage over the rate-control strategy. Eighteen years later, EAST-AFNET 4 showed that the rhythm-control approach is better than rate control in reducing adverse cardiovascular outcomes in patients with a recent diagnosis of atrial fibrillation (AF). During the time between AFFIRM and EAST-AFNET 4, rhythm control understanding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…By doing so, it is possible to lower the risk of stroke and other heart-related complications associated with AF, especially for selected patients 1 . Moreover, this focus on early rhythm management has largely resolved the longstanding controversy of whether to prioritize rhythm control or rate control, thus shifting the paradigm of AF treatment from 'better symptoms control' to reducing the incidence of MACCE 23 .…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, it is possible to lower the risk of stroke and other heart-related complications associated with AF, especially for selected patients 1 . Moreover, this focus on early rhythm management has largely resolved the longstanding controversy of whether to prioritize rhythm control or rate control, thus shifting the paradigm of AF treatment from 'better symptoms control' to reducing the incidence of MACCE 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the next two decades, PV isolation became the gold standard of AF ablative treatment and we saw a vivid and rapid improvement in techniques and technologies aiming to a durable and, at the same time, safer and faster PV lesions. Moreover, during this period we testified also a growing enthusiasm toward AF ablation supported by trials (CABANA and its substudies, and EAST-AFNET4) demonstrating that rhythm control—especially when achieved by ablation—improves outcomes over the only rate control and thus refusing the previous dogma according to which there were no differences in outcomes between rate and rhythm control (AFFIRM) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Clinical evidence is also going towards the demonstration that the best rhythm strategy control is ablative and not pharmacological, above all if performed as soon as possible, in an early stage to avoid the onset of an irreversible and self-feeding atrial cardiomyopathy.…”
Section: Introductionmentioning
confidence: 92%
“…A meta-analysis of randomized controlled trials (RCTs) comparing rate control and rhythm control strategies for AF found no significant differences in mortality or stroke rates between the 2 strategies but showed that the rate control strategy was associated with a lower risk of adverse events [14] . Therefore, rate control is the preferred strategy for most patients with AF, particularly those with comorbidities or who are older [15] .…”
Section: Rate Controlmentioning
confidence: 99%